(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
The article examined the role of state policy in reducing poverty and ensuring youth employment in the context of modern globalization. The study analyzed the effectiveness of investing in human capital, education and skills development, progressive taxes, social programs, microcredit, and targeted programs.